2012
DOI: 10.1155/2012/527607
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins as PPARγModulators in Adipogenesis

Abstract: Adipocytes and fat cells play critical roles in the regulation of energy homeostasis. Adipogenesis (adipocyte differentiation) is regulated via a complex process including coordinated changes in hormone sensitivity and gene expression. PPARγ is a ligand-dependent transcription factor and important in adipogenesis, as it enhances the expression of numerous adipogenic and lipogenic genes in adipocytes. Prostaglandins (PGs), which are lipid mediators, are associated with the regulation of PPARγ function in adipoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 77 publications
3
37
0
Order By: Relevance
“…18 Different prostaglandins may activate or suppress adipogenesis depending on the effect they have on the PPARγ pathway. 19 Notably, in regards to the present study, prostaglandin F2α downregulates the adipogenic effects of PPARγ. 20,21 Thus, prostaglandin F2α—the active agent in bimatoprost and used for lowering IOP in glaucoma patients—can downregulate adipogenesis via a central regulatory pathway in the inflammatory cascade involved in TED.…”
Section: Discussionsupporting
confidence: 44%
“…18 Different prostaglandins may activate or suppress adipogenesis depending on the effect they have on the PPARγ pathway. 19 Notably, in regards to the present study, prostaglandin F2α downregulates the adipogenic effects of PPARγ. 20,21 Thus, prostaglandin F2α—the active agent in bimatoprost and used for lowering IOP in glaucoma patients—can downregulate adipogenesis via a central regulatory pathway in the inflammatory cascade involved in TED.…”
Section: Discussionsupporting
confidence: 44%
“…The activation of PPARγ by its endogenous ligand promotes adipocyte hypertrophy 19 . In addition, although the gene expression ratio of the mb75 group was less than 2 compared to that of the other three groups, the major lipid metabolism-related genes were shown in Table 13.…”
Section: Discussionmentioning
confidence: 99%
“…As shown Table 9, the rate of linoleic acid was large and the rate of arachidonic acid 20:4 n-6 was lowest in mb75 group, so it was considered that the Δ6-desaturase activity in mb75 group is low 14 . Hence, it was suggested that the generation of endogenous ligands on PPARγ is less 19,20 . Moreover, these changes in fatty acid composition was also observed in serum and liver.…”
Section: Discussionmentioning
confidence: 99%
“…40 PPARg-dependent adipocyte formation is regulated by prostaglandins (PG), a family of endogenous bioactive lipids that signal via G-protein-coupled receptors. 42 Overexpression of cyclooxygenases (COX), which catalyze the rate-limiting step of PG synthesis, in pre-adipocytes, suppresses subsequent differentiation. 43 Members of the PG family have versatile effects on adipocyte formation.…”
Section: Adipocyte Differentiation -Regulation By Lipidsmentioning
confidence: 99%
“…For example, PGI2 activates adipose progenitors to promote differentiation, PGE2 and PGF2a are early-phase negative regulators of differentiation, while PGD2 and derivatives of PGJ2 are late-phase positive regulators of differentiation. 42 One of the key hormones that promote adipocyte differentiation and lipogenesis is insulin. 2,3,37,40 Fatty acids are capable of regulating insulin sensitivity in differentiating adipocytes.…”
Section: Adipocyte Differentiation -Regulation By Lipidsmentioning
confidence: 99%